Mechanism of ultrasonic vibration assisted upsetting of 6061 aluminum alloy. (November 2020) - Cao, M.Y.; Hu, H.; Jia, X.D.; Tian, S.J.; Zhao, C.C.; Han, X.B.
Abstract: Ultrasonic vibration-assisted forming technology has the advantages of enhanced forming limit and reduced forming load. An ultrasonic vibration (UV) upsetting experiment is designed and carried out in this study to explore the law and the mechanism of "volume effect" and "surface effect" under UV. The results of the "volume effect" indicate that after UV is applied, the stress of the material is decreased instantly, and the stress reduction level becomes proportional to the ultrasonic vibration amplitude. The maximum decreasing amount is 31.67 % when the amplitude is 2.96 μm. A hybrid constitutive modeling is established on the basis of nonlocal theory, dislocation evolution theory, and thermal activation theory. The model is in good agreement with the experimental results. Then, after the UV is stopped, the flow stress is recovered along the elastic path, and a stress tip appears at the end of the recovery. The results of the "surface effect" indicate that UV can refine the grain and increase the proportion of the contact surface's bright area. The bright area increases to 32.37 % when the amplitude is 2.96 μm. After the UV is applied, the friction coefficient between the contact interfaces is considerably reduced. The friction coefficient is reduced to 39.4 % in our experiment.